Inovasi Digital dan Kepercayaan Publik: Riset Persepsi dan Analisis Pada Layanan Pembayaran Pajak Kendaraan Bermotor - Busri, Busri; Haning, Mohamad Thahir (Kybernology : Journal of Government Studies, 2024)
Public trust plays an important role in forming a productive and responsive government, especially when the government faces pressure to provide effective services with limited resources. This study analyzes public trust in motor vehicle tax payment services in Pinrang Regency. This study uses a mixed research approach, qualitative data collection through semi-structured interviews with the community and employees at the UPT Samsat Pinrang about the factors that influence public trust and researcher observations for three months at the service office. A survey of public satisfaction with the service was conducted from July to September 2024 showing that the length of service was considered lacking, resulting in a perception of dissatisfaction (value 2.63 on a scale of 4.00). Indicators of credible commitment include consistent implementation of SOPs, digital innovation even though access to technology is still a challenge, service principles based on smiles and greetings, and the use of regional languages to build good relationships. Honesty is reflected in the openness of cost information, although there is still a stigma of extortion due to lack of socialization. Employee competence is seen from mastery of technology, regulations, and interpersonal skills. Justice is realized through transparent queues, although it still faces obstacles from brokers and the stigma of "insider". This study provides insights into the role of digital innovation and the importance of interpersonal approaches for frontline bureaucrats in enhancing public trust.